From dispassionate law to compassionate outcomes in health-care law, or not. Issue 2 (12th May 2017) - Biggs, Hazel
Abstract: Health-care law presents numerous challenges to the conception of the law as a dispassionate arbiter of disputes or protector of rights. Issues relating to end-of-life care, the assessment of mental capacity and decision-making for those who lack capacity, amongst others, epitomise the complex nature of health-care law. They also raise globally applicable questions about discrimination, or equal protection, as well as concerns for relief of suffering, the assessment of best interests and the exercise of individual autonomy. This paper will evaluate the extent to which law's traditional objectivity (dispassion) is undermined by the introduction of concerns about compassion into judicial and executive decisions. Focusing primarily on the law in England and Wales, but with reference to multi-jurisdictional case-law and international instruments, it will consider whether the law provides compassionate approaches and outcomes in end-of-life decision-making, and the implications of compassion for legal certainty.